Expression and function of K(ATP) channels in normal and osteoarthritic human chondrocytes: possible role in glucose sensing - Rufino, Ana T. (2013)
ATP‐sensitive potassium [K(ATP)] channels sense intracellular ATP/ADP levels, being essential components of a glucose‐sensing apparatus in various cells that couples glucose metabolism, intracellular ATP/ADP levels andmembrane potential. These channels are present in human chondrocytes, but their subunit composition and functions are unknown. This study aimed at elucidating the subunit composition of K(ATP) channels expressed in human chondrocytes and determining whether they play a role in regulating the abundance of major glucose transporters, GLUT‐1 andGLUT‐3, and glucose transport capacity. The results obtained show that human chondrocytes express the pore forming subunits, Kir6.1 and Kir6.2, at the mRNA and protein levels and the regulatory sulfonylurea receptor (SUR) subunits, SUR2A and SUR2B, but not SUR1. The expression of these subunits was no affected by culture under hyperglycemia‐like conditions. Functional impairment of the channel activity, using a SUR blocker (glibenclamide 10 or 20 nM), reduced the protein levels of GLUT‐1 and GLUT‐3 by approximately 30% in normal chondrocytes, while in cells from cartilage with increasing osteoarthritic (OA) grade no changes were observed. Glucose transport capacity, however, was not affected in normal or OA chondrocytes. These results show that K(ATP) channel activity regulates the abundance of GLUT‐1 and GLUT‐3, although other mechanisms are involved in regulating the overall glucose transport capacity of human chondrocytes. Therefore, K(ATP) channels are potential components of a broad glucose sensing apparatus thatmodulates glucose transporters and allows human chondrocytes to adjust to varying extracellular glucose concentrations. This function of K(ATP) channels seems to be impaired in OA chondrocytes.